Tactics of Catholic Religious Education Teachers in Implementing Students' Disciplinary Character at SMP Negeri 1 Namorambe - Tibo, Paulinus; Iskandar, Benny (CV. Rayyan Dwi Bharata, 2024)
This research studies the tactics used by PAK teachers in implementing character education for students. Education has an important role in the current era, especially in character development which is very important for the nation's generation. Emphasis on character education aims to teach values such as discipline, which can change students' behavior to be more positive. In addition, character education forms habits that are in accordance with social norms. This research uses a qualitative descriptive method. The data collection process used observation and interviews with PAK teachers in junior high schools. The results showed that the role of PAK teachers in implementing disciplinary character towards students using strategies such as strengthening religious values, applying consistent punishments, and providing examples through daily life have shaped students' character.